A ZrN nanocrystalline coating for polymer electrolyte membrane fuel cell metallic bipolar plates prepared by reactive sputter deposition1. Issue 82 (5th September 2015) - Xu, Jiang; Xu, Song; Munroe, Paul; Xie, Zong-Han
<x xml:space="preserve">Abstract</x> A ZrN coating with an average grain size of ∼15 nm, was employed to improve the surface performance and durability of 316L stainless steel (SS) used in polymer electrolyte membrane fuel cells (PEMFCs) environments.